Multi-scale habitat selection by mountain caribou in West Central Alberta - Szkorupa, Tara; Schmiegelow, Fiona (Rangifer, 2003)
This research suggests that mountain caribou select a suite of winter habitats, at multiple spatial scales, and under a range of snow conditions. Our findings lead to several management recommendations. In general, habitat selection by caribou necessitates management over large spatial and temporal scales.